UPAYA MENINGKATKAN KEMAMPUAN MENGANALISIS PESERTA DIDIK, MELALUI PENERAPAN MODEL PBL KOLABORASI THINK PAIR AND SHARE - Mar’atun, Umi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to improve the analytical skills of class X Mipa 3 students at SMA Negeri 4 Semarang Semester 2 for the 2021/2022 academic year. The ability to analyze students is low before being given action in class, the teacher has tried several solutions for solving it for Class X Mipa 3 students, but the results have not fully overcome the problem, namely increased analytical ability. The subject of class action implementation was class X Mipa 3 SMA Negeri 4 Semarang Semester 1, totaling 36 students. This research data was collected through sources, places, and learning events. Data collection techniques with interview and observation methods. The procedure in this classroom action research was carried out through two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. This classroom action research is expected to increase the ability to analyze students at least 85% of 36 students. The results of this study indicate that the level of ability to analyze students of class X Mipa 3 SMA Negeri 4 Semarang, namely those who have the ability to analyze in learning according to the indicators that have been set before conducting class action research is still low, only 13 students (36%). After the action in cycle I, the ability to analyze increased to 23 students (63%) and in cycle II it increased to 31 students (87%). Based on the data from the results of this class action research, it is proven that through the use of the Problem Based Learning model, the collaboration of the Think Pair and Share method can improve the Analytical Ability of Class X Mipa 3 Students of SMA Negeri 4 Semarang Semester 2 for the 2021/2022 academic year.